2021
DOI: 10.13057/biodiv/d220336
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of forest degradation condition in Natmataung National Park Watershed, Myanmar

Abstract: Abstract. Oo Y, Suanpaga W, Muenpong P. 2021. Assessment of forest degradation condition in Natmataung National Park Watershed, Myanmar. Biodiversitas 22: 1354-1362. Natmataung National Park (NTNP) is an important biodiversity hotspot in Myanmar, yet it is threatened by various anthropogenic activities, leading to deforestation and forest degradation. As such, the park needs to be restored to bring back its main function of conserving biodiversity. Ecological restoration in NTNP needs assessment of forest rest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
0
0
Order By: Relevance
“…Te dominance range (15.0-20.6 m 2 •ha −1 ) in this study was well comparable to the value reported for the human-disturbed forest (17.77-24.47 m 2 •ha −1 ) in the Popa Mountain Park [27]. However, it was much lower than those recorded in the Alaungdaw Kathapa National Park (60.03 m 2 •ha −1 ) [25] and the Natmataung National Park (55.63 m 2 •ha −1 ) [65], which have been protected since 1984 and 1994 in upper Myanmar.…”
Section: Do Tree Density Dominance and Diversity Difer Between Bucf A...supporting
confidence: 88%
See 1 more Smart Citation
“…Te dominance range (15.0-20.6 m 2 •ha −1 ) in this study was well comparable to the value reported for the human-disturbed forest (17.77-24.47 m 2 •ha −1 ) in the Popa Mountain Park [27]. However, it was much lower than those recorded in the Alaungdaw Kathapa National Park (60.03 m 2 •ha −1 ) [25] and the Natmataung National Park (55.63 m 2 •ha −1 ) [65], which have been protected since 1984 and 1994 in upper Myanmar.…”
Section: Do Tree Density Dominance and Diversity Difer Between Bucf A...supporting
confidence: 88%
“…Our study showed that the ZNP requires efective conservation compared to species richness in other protected areas in Myanmar [25,26,65]. However, the proximity of the sample plots to human-dominated areas may explain the restricted diversity of the species.…”
Section: Consequences For Conservation Inside and Outside Of Thementioning
confidence: 76%
“…This can be done by planting pioneer or fast-growing exotic species found in the original forest in the degraded forest areas. This would help shorten the succession phase of plant community by increasing the species composition and biodiversity [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%